Influência da periodontite apical no perfil hematológico de ratos Wistar portadores de aterosclerose: estudo preliminar - Martins, Marina Ottoni [UNESP] (2018)
This study evaluated the influence of apical periodontitis (PA) on the hematological profile of normal or atherosclerosis (AT) rats. Forty male Wistar rats were distributed in 4 groups of 10 animals: control rats (C); rats with apical periodontitis (PA); rats with atherosclerosis (AT); rats with AP and atherosclerosis (PA+AT). Atherosclerosis was induced surgically, by means of an artificial ligation made around the common carotid artery stenosis inner diameter of 0.3mm. One day after surgery, it was administered a dose of vitamin D3 for two days (90,000 IU). The surgically induced animals were fed a hyperlipid diet consisting of a conventional diet associated with 20% lard and 5% sugar throughout the experimental period. After 30 days, the apical periodontitis was induced by exposing the coronary pulp of the first and second upper and lower right molars to the oral medium. After another 30 days, cardiac puncture was performed to remove the hematological tissue, and then the animals were euthanized. Hemoglobin, hemoglobin, hemoglobin, mean corpuscular volume (MCV), mean corpuscular hemoglobin concentration (CHCM), leukocytes, neutrophils, lymphocytes, monocytes, eosinophils, basophils, platelets, and total plasma protein (PPT). The results obtained were statistically analyzed by Kruskall Wallis and Dunn tests with a significance level of 5% (p <0.05). There was a reduction in the number of leukocytes and basophils in the groups with atherosclerosis (AT and PA+AT), but without significant difference between groups (p <0.05). The PA+AT group had a lower neutrophil value, but no significant difference compared to the other groups (p <0.05). There were fewer monocytes in the groups presenting isolated or associated alterations (PA, AT and PA+AT), when compared to the control group (p <0.05). Eosinophils and Total Plasma Protein significantly reduced in the atherosclerosis groups relative to the control...